2020
DOI: 10.1038/s41392-020-0137-7
|View full text |Cite
|
Sign up to set email alerts
|

NUSAP1 potentiates chemoresistance in glioblastoma through its SAP domain to stabilize ATR

Abstract: NUSAP1, which is a microtubule-associated protein involved in mitosis, plays essential roles in diverse biological processes, especially in cancer biology. In this study, NUSAP1 was found to be overexpressed in GBM tissues in a grade-dependent manner compared with normal brain tissues. NUSAP1 was also highly expressed in GBM patients, dead patients, and GBM cells. In addition, NUSAP1 was found to participate in cell proliferation, apoptosis, and DNA damage in GBM cells. Ataxia telangiectasia and Rad3related pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 46 publications
0
42
0
Order By: Relevance
“…Cells were collected and then lysed in a RIPA lysis buffer with phenylmethanesulfonyl fluoride (PMSF) as previously described [ 31 ]. Protein concentration was detected with a BCA protein assay kit.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were collected and then lysed in a RIPA lysis buffer with phenylmethanesulfonyl fluoride (PMSF) as previously described [ 31 ]. Protein concentration was detected with a BCA protein assay kit.…”
Section: Methodsmentioning
confidence: 99%
“…The shNUCKS sequences (Table S1 ) were inserted into the pLKO.1 vector. As described previously, the cDNA sequence of human NUCKS was purchased from Youbio Biological Technology Co., Ltd. (Changsha, China), which was cloned into the pCDH-CMV-MCS-EF1-GFP-Puro vector provided by GeneCreate (Wuhan, China) [ 27 ]. The Beclin1 shRNA plasmid was purchased from Sigma-Aldrich (TRCN0000299864), and the plasmid GFP-LC3B [ 28 ] was a gift from Prof. Ning Gao at the Third Military Medical University, China.…”
Section: Methodsmentioning
confidence: 99%
“…17 Accumulating evidence have indicated that abnormal expression of NUSAP1 was implicated in tumorigenesis, drug resistance and patient survival. [18][19][20] Li et al reported that NUSAP1 contributed to cervical cancer via stimulating cancer stem cell (CSC) traits and facilitating epithelialmesenchyme transition (EMT) progression via Wnt/βcatenin signaling. 21 Furthermore, Okamoto et al found that NUSAP1 expression was upregulated in Oral Squamous Cell Carcinoma (OSCC)-derived cell lines and knockdown of NUSAP1 inhibited cell proliferation and also promoted anti-tumor effect of Paclitaxel by inducing apoptosis in OSCC.…”
Section: Dovepressmentioning
confidence: 99%